Economic diplomacy: deciphering the case of Sino-Pakistani economic relations - Jarral, Khalid (2022)
This thesis engages with the debates about diplomatic agency in the realist conception of diplomacy and strategic interests as factors shaping contemporary economic diplomacy by focusing on the case of Sino-Pakistani economic cooperation. This research has examined the previously unexplored areas of the relevance of the military actors to the management of economic relations between states and economic cooperation for shared strategic goals based on the location of a state’s territory.